2021
DOI: 10.4018/ijoci.2021010105
|View full text |Cite
|
Sign up to set email alerts
|

Solving a Business Process Optimization Issue With a Genetic Algorithm Coupled With Multi-Criteria Decision Analysis Method

Abstract: The addressed issue in the present work revolves around the area of business process management in general and in particular optimization. The problem involves the generation of optimized business process designs from a business process model in a multi-criteria optimization environment by appealing an evolutionary algorithm. Thus, the main contribution is to analyze the characteristics of using a multi-criteria decision-analysis method within a genetic algorithm in an issue of business process optimization. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The experimental results are promising in the sense that the proposed framework is capable of producing an acceptable number of optimized design alternatives regarding the problem complexity and in a reasonable period. The benefits of using a multicriteria decision analysis method within a genetic algorithm for BPO are also evident in [33]. The experimental results clearly demonstrated that using a multicriteria decision-analysis method provably facilitates the production of qualitatively interesting alternative solutions in a short period time, a fact that ultimately assists in the decision-making procedure.…”
Section: Related Workmentioning
confidence: 76%
“…The experimental results are promising in the sense that the proposed framework is capable of producing an acceptable number of optimized design alternatives regarding the problem complexity and in a reasonable period. The benefits of using a multicriteria decision analysis method within a genetic algorithm for BPO are also evident in [33]. The experimental results clearly demonstrated that using a multicriteria decision-analysis method provably facilitates the production of qualitatively interesting alternative solutions in a short period time, a fact that ultimately assists in the decision-making procedure.…”
Section: Related Workmentioning
confidence: 76%